PENYERAPAN LOGAM Pb2+ SECARA BIOLOGIS OLEH BAKTERI Escherichia coli - Muhammad Sigit Ariski; Rudi Kartika; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2025)
The biological absorption of Pb2+ metal by Escherichia coli bacteria has been conducted. This study aims to determine the ability of Escherichia coli bacteria to absorb Pb2+ metal based on variations in Pb2+ exposure concentrations (0, 3, 6, 9, 12, 15 ppm) over different exposure times (days) and to identify the optimal concentration and time required for Escherichia coli in the biological absorption of Pb2+ metal. The maximum wavelength of the standard Pb2+ solution is 520 nm. Based on the test results, Escherichia coli was able to absorb Pb2+ at varying exposure concentrations (3, 6, 9, 12, 15 ppm) with biosorption percentages of 49.118%, 23.985%, 14.500%, 10.150%, and 7.808%, respectively. The optimal concentration and time required for Escherichia coli to absorb Pb2+ occurred on the 3rd day with a Pb2+ exposure concentration of 3 ppm. Keywords: Biosorption, Pb2+ metal, Escherichia coli